2023
DOI: 10.1093/eurheartj/ehad056
|View full text |Cite
|
Sign up to set email alerts
|

Rule-out of non-ST-segment elevation acute coronary syndrome by a single, pre-hospital troponin measurement: a randomized trial

Abstract: Aims Patients with suspected non-ST-segment elevation acute coronary syndrome (NSTE-ACS) are routinely transferred to the emergency department (ED). A clinical risk score with point-of-care (POC) troponin measurement might enable ambulance paramedics to identify low-risk patients in whom ED evaluation is unnecessary. The aim was to assess safety and healthcare costs of a pre-hospital rule-out strategy using a POC troponin measurement in low-risk suspected NSTE-ACS patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 27 publications
0
18
0
2
Order By: Relevance
“…The Royal Free Hospital managed to reduce median time to ICA through this pathway to 2.8 h (IQR 1.5–9) compared to 60 h (IQR 33–116) with use of a pathway similar to the pathway evaluated in our study 2 . Additionally, a two recently conducted randomized trials by Camaro et al 18 and Dawson et al 19 demonstrated that prehospital rule‐out of ACS with a point‐of‐care troponin measurement in chest pain patient's notably reduced healthcare expenditure. However, there is not yet consensus on the most ideal form of prehospital triage as several methods are still in the early stages of development and trials are currently being conducted 20 .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The Royal Free Hospital managed to reduce median time to ICA through this pathway to 2.8 h (IQR 1.5–9) compared to 60 h (IQR 33–116) with use of a pathway similar to the pathway evaluated in our study 2 . Additionally, a two recently conducted randomized trials by Camaro et al 18 and Dawson et al 19 demonstrated that prehospital rule‐out of ACS with a point‐of‐care troponin measurement in chest pain patient's notably reduced healthcare expenditure. However, there is not yet consensus on the most ideal form of prehospital triage as several methods are still in the early stages of development and trials are currently being conducted 20 .…”
Section: Discussionmentioning
confidence: 74%
“…The Royal Free Hospital managed to reduce median time to ICA through this pathway to 2.8 h (IQR 1.5-9) compared to 60 h (IQR 33-116) with use of a pathway similar to the pathway evaluated in our study 2. Additionally, a two recently conducted randomized trials by Camaro et al18 and Dawson et al19 demonstrated that prehospital rule-out of ACS with a point-of-care troponin…”
mentioning
confidence: 57%
“…In low-risk patients, a single high-sensitivity troponin has been sufficient to ‘rule out’ acute coronary syndrome (ACS) in the ED. This multicentre, open-label, randomised controlled trial (RCT) across five ambulance regions in the Netherlands assessed if the use of a prehospital point-of-care (POC) troponin in low-risk patients with chest pain could significantly reduce 30-day healthcare costs 2…”
Section: Rule-out Of Non-st-segment Elevation Acute Coronary Syndrome...mentioning
confidence: 99%
“…It is expected that new high-sensitive point-of-care troponin devices can even further improve the safety of prehospital stratification [5][6][7]. The recent ARTICA trial showed that this is also costeffective [8]. This way, up to 20-30% of patients who call the emergency telephone number for the Netherlands (112) because of chest pain can safely stay at home.…”
mentioning
confidence: 99%
“…Hospitals are experts at ruling out diseases and work more defensively: often additional CT scans, laboratory tests and even cardiac catheterisations are performed on these low-risk patients, without additional value but at a cost of about 7500 euro per patient. It is estimated that 30-50 million euro could be saved nationwide when these unnecessary hospital admissions are prevented [8,11].…”
mentioning
confidence: 99%